Detection of a pair of outliers in a sample from a Gumbel distribution with known scale parameter. Issue 2 (25th January 2018) - Lalitha, S.; Tripathi, Pratyasha
ABSTRACT: Test procedures on outlier detection problems for Gumbel distribution are rarely available. Hence, a test statistic is proposed here for detection of a pair of upper and lower outliers from a Gumbel distribution with known scale parameter. The critical values of the statistic are obtained and some examples are also given to highlight the use of the statistic. The advantage of the proposed statistic is that the scale parameter, though assumed to be known is not explicitly involved in the determination of the critical values.